Belief, Social Identity, and Sexually Transmitted Infection Risks Among UWEC Students - Fredrick, Bryton (My University, 2012)
This study assesessed student knowledge of and social norms about the risks of various sexual practices.
Color poster with text, graphs, and tables.
Keywords: Group identity; Sexually transmitted diseases--Social aspects; College students--Wisconsin--Eau Claire--Attitudes--Surveys; Posters